Pengembangan Multimedia Interaktif Berbasis Prezi di SMK Negeri 1 Tanjung Raya - Novia Susanti; Elfizon Elfizon (Universitas Negeri Padang, 2019)
This paper aimed to produce Prezi-based learning media on the material to analyze a series of magnetism that is valid, practical and effective. One multimedia that can be developed is Prezi, which has the advantage of having a virtual canvas. All ideas are contained in one canvas, both text, audio, video and all learning material. This research method is a development study that uses 4-D models, which consist of the stages of define, design, develop and assess. The resulting media are categorized as valid with an average validity level of 87.81%. The practicality of the media by teachers and students has an average value of 95.14% and 91.99% with a very practical category in terms of learning activities, ease of use and benefits. As for the results of the effectiveness testing it was concluded that interactive multimedia that was developed was effectively used as one of the learning media with the classical completeness of students 96.67%. So it can be concluded that Prezi-based interactive multimedia for students of class X TITL Vocational School on analyzing the magnetic circuit is declared valid, practical and effective.